Church and cloister of the Holy Trinity Church of the Minorites in Vienna, in the Alservorstadt (also known as the Weissspanier). - Corvinus, Johann August, 1683-1738 (engraver):::Creator::::::::::::; Kleiner, Salomon, 1700-1761 (artist):::Contributor:::::::::::: (Vienna?; J.A. Pfeffel; Austria, 2020)
Handcolored copper engraving of the Church and cloister of the Holy Trinity Church of the Minorites in Vienna, in the Alservorstadt (also known as the Weissspanier). Key to images in caption: a. Domus Langheiminana. b. nova domus in horto Nadelmeyriano=a. Das Langheimische Haus. b. Das neue Haus im Nadelmeyrischen Garten.